2008
DOI: 10.1128/mcb.02227-07
|View full text |Cite
|
Sign up to set email alerts
|

Rhythmic SAF-A Binding Underlies Circadian Transcription of the Bmal1 Gene

Abstract: Although Bmal1 is a key component of the mammalian clock system, little is understood about the actual mechanism of circadian Bmal1 gene transcription, particularly at the chromatin level. Here we discovered a unique chromatin structure within the Bmal1 promoter. The RORE region, which is a critical cis element for the circadian regulation of the Bmal1 gene, is comprised of GC-rich open chromatin. The 3-flanking region of the promoter inhibited rhythmic transcription in the reporter gene assay in vitro even in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
63
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(67 citation statements)
references
References 48 publications
4
63
0
Order By: Relevance
“…Previous reports have indicated that SAF-A interacts with gene promoters and its interaction is controlled by external factors for example circadian rhythm (Ahmad and Lingrel, 2005;Gao et al, 2005;Onishi et al, 2008;Zhao et al, 2009 (Kim and Nikodem, 1999;Kukalev et al, 2005). Using in situ PLA and co-IP we confirm that SAF-A interacts with RNA pol II in ES cells.…”
supporting
confidence: 69%
“…Previous reports have indicated that SAF-A interacts with gene promoters and its interaction is controlled by external factors for example circadian rhythm (Ahmad and Lingrel, 2005;Gao et al, 2005;Onishi et al, 2008;Zhao et al, 2009 (Kim and Nikodem, 1999;Kukalev et al, 2005). Using in situ PLA and co-IP we confirm that SAF-A interacts with RNA pol II in ES cells.…”
supporting
confidence: 69%
“…Perhaps as a binder of both DNA and RNA, SP120 plays multiple roles in transcriptional regulation, both in repression and activation (23)(24)(25)(26). The protein appears to be a pleiotropic regulator of gene expression and is very likely to take an important part in additional systems, as well.…”
Section: Discussionmentioning
confidence: 99%
“…Both Xist RNA and SAF-A have been detected in the nuclear matrix fraction after removal of chromatin (Clemson et al, 1996;Helbig and Fackelmayer, 2003). Saf-A has been implicated in many processes, including transcription, RNA transport, DNA replication and circadian rhythm (Onishi et al, 2008). Saf-A is required for cell proliferation and a hypomorphic mutation in mice causes embryonic lethality (Roshon and Ruley, 2005).…”
Section: Saf-a Ash2l and Macroh2a Recruitment Requiresmentioning
confidence: 99%